The analysis of lysine succinylation modification reveals the mechanism of oxybenzone damaging of pakchoi (Brassica rapa L. ssp. chinensis) - Li, Shuhao; Zhou, Yuqi; Xu, Yang; Ran, Shengxiang; Hou, Maomao; Li, Qingming; Zhong, Xin; Zhong, Fenglin (Frontiers in Plant Science, 2022)
Oxybenzone (OBZ), one of a broad spectrum of ultraviolet (UV) absorbents, has been proven to be harmful to both plants and animals, while omics analysis of big data at the molecular level is still lacking. Lysine succinylation (Ksuc) is an important posttranslational modification of proteins that plays a crucial role in regulating the metabolic network in organisms under stress. Here, we report the changes in intracellular Ksuc modification in plants under OBZ stress. A total of 1276 succinylated sites on 507 proteins were identified. Among these sites, 181 modified proteins were hypersulfinylated/succinylated in OBZ-stressed pakchoi leaves. Differentially succinylated proteins (DSPs) are distributed mainly in the chloroplast, cytoplasm, and mitochondria and are distributed mainly in primary metabolic pathways, such as reactive oxygen species (ROS) scavenging, stress resistance, energy generation and transfer, photosynthetic carbon fixation, glycolysis, and the tricarboxylic acid (TCA) cycle. Comprehensive analysis shows that Ksuc mainly changes the carbon flow distribution, enhances the activity of the antioxidant system, affects the biosynthesis of amino acids, and increases the modification of histones. The results of this study first showed the profiling of the Kusc map under OBZ treatment and proposed the adaptive mechanism of pakchoi in response to pollutants and other abiotic stresses at the posttranslational level, which revealed the importance of Ksuc in the regulation of various life activities and provides a reference dataset for future research on molecular function.